Airbnb as a sharing economy-enabled digital service platform: The power of motivational factors and the moderating role of experience. Issue 3 (May 2022) - Tumer Kabadayi, Ebru; Cavdar Aksoy, Nilsah; Yazici, Nihal; Kocak Alan, Alev
Airbnb is one of the business models that represent the expansion of the sharing economy into digital environments. The model offers several different benefits to its own customers, who are guests and hosts. It affects the tourism and hospitality industry via its economic impact on competition and its influence on choices made by visitors. This study thus aims to explore the role of visitor motivation to use Airbnb (price value, authenticity, enjoyment, social interaction, home benefits, novelty, and sharing economy ethos) and the visitor experience (low-experienced vs. high-experienced individuals) by explaining usage intention via attitudes toward this particular business model. For this purpose, 468 people were surveyed online, and the gathered data were analyzed using structural equation modeling. Based on the results, we can offer empirical evidence of the positive effect of motivational factors on attitude, and correspondingly, also of attitude on usage intention. The moderating role of experience on the relationship between motivation and attitude is also discussed.